On the Margins of Death: A Scoping Review on Palliative Care and Schizophrenia. Issue 1 (January 2019) - Relyea, Erin; MacDonald, Brooke; Cattaruzza, Christina; Marshall, Denise
Schizophrenia is a serious chronic mental illness that results in marginalization and stigma for sufferers. It is the seventh leading cause for disability worldwide. The symptoms of the illness, including hallucinations, delusions, and extremely disordered thinking and behavior, may also introduce barriers to accessing treatment, education, housing, and employment. Little is known about end-of-life care for individuals with schizophrenia. To address this gap, a scoping review was conducted to enhance understanding of hospice and palliative care for patients with schizophrenia. From this scoping review, 342 unique titles and abstracts were identified through a search of 20 databases, including 11 social science databases, 6 medical databases, and 3 gray literature databases. A total of 32 articles met the inclusion criteria and the following 4 themes were identified: Stigma affecting quality of care and access to care; Issues related to consent and capacity for the patient's end-of-life care decisions and to appoint substitute decision makers; Best practices for psychosocial interventions, pharmacology, family and health-care collaborations, goals of care, setting, and smoking; and Barriers to care, including setting, communication, provider education, and access to care. The review suggests the importance of mandatory interdisciplinary training practices and policy standards outlining cooperative communication across health-care providers. It highlights gaps in evidence-based research on psychosocial interventions and collaborative frameworks to enable the provision of quality end-of-life care for individuals with schizophrenia.